Aspek Maslahah Terhadap Program Sunset Policy Pemerintah Kota Malang - Aris Nur Mu'allim (Journal of Islamic Business Law, 2017)
This research was conducted to find out the background of the issuance of sunset policy program by Malang city government and its mashlahah aspect. This study is an empirical research that uses a conceptual approach by using the concept of mashlahah that exist in Islam. Primary data in the form of interviews with some informants and secondary data in the form of books related to the concept of mashlahah. The result of this research is that sunset policy program is issued as a form of settlement effort of tax collection of Land and Building Tax of Malang city taxpayer which is part of delegation of authority of Land and Building Tax which done in the year 2013 ago preceded by census and cleansing. Sunset policy program provides benefits for city residents of Malang, especially taxpayers who pay late urban PBB in the form of lenient fees they have to pay. They only pay the principal of the PBB Urban taxes alone without the administrative sanction in the form of a fine of 2% of the tax principal to be paid. As for the city of Malang, the benefits obtained in the form of reduction of urban PBB receivables taxpayer Malang city. Sunset policy program has met the requirements mashlahah so it can be said as a Mashlahah. Keywords: Land and Building Tax, Sunset policy, and Mashlahah.